A protocol for a systematic review of the diagnostic accuracy of blood markers, synovial fluid, and tissue testing in periprosthetic joint infections (PJI). Issue 1 (December 2015) - Beaule, Paul; Shea, Beverley; Abedlbary, Hesham; Ahmadzai, Nadera; Skidmore, Becky; Mallick, Ranjeeta; Hutton, Brian; Bunting, Alexandra; Moran, Julian; Ward, Roxanne; Moher, David
Abstract Background Total joint replacement (TJR) procedures have been one of the most rewarding interventions for treating patients suffering from joint disease. However, developing a periprosthetic joint infection (PJI) is a serious complication that is associated with the highest burden of cost and reduction in patients' quality of life compared to other complications following TJRs. One of the main challenges facing clinicians who are treating PJIs is accurately diagnosing infection in a timely fashion. Multiple orthopedic associations have published clinical guidelines for diagnosing PJI which are based solely on consensus approaches, expert opinions, and narrative reviews. We believe that a higher quality of scientific rigor is necessary to establish a diagnostic guideline that represents current evidence more accurately and that identifies important knowledge gaps in PJI diagnosis. Therefore, we will conduct a systematic review on diagnostic performance of blood markers, synovial fluids, and tissue tests for diagnosing PJI. Methods/design Electronic search strategies will be developed and tested by an experienced medical information specialist in consultation with the review team, and gray literature will be searched using the checklist from CADTH's Grey Matters Light. Two reviewers will independently screen the literature for inclusion using the prespecified eligibility criteria. Non-English language and animal-only studies will be excluded. Quality assessment and data extractions by reviewers will be verified, and disagreements will be resolved through consensus or third party adjudication. We will assess the quality of individual studies using the QUADAS-2 tool and use GRADE to summarize the strength of body of evidence. Analyses of evidence will be conducted in accordance with theCochrane Handbook for Diagnostic Test Accuracy Reviews . Discussion We will conduct a systemic review of tests (blood markers, synovial fluids, and tissue testing) for diagnosing PJI in patients' knee, hip, and shoulder joint replacements. This will be the first scientifically rigorous and comprehensive systematic review in the field and may feed into an evidence-based clinical practice guideline. We will compare the findings of this review with the consensus-based guides and discuss the differences, similarities, and knowledge gaps. Systematic review registration PROSPEROCRD42015023768